Peritoneal dialysis catheter placement with percutaneous technique with fluoroscopic guidance - our centers experience - Silva,Joana R (2018)
Introduction: Studies have shown no clear superiority between surgical and percutaneous methods for peritoneal dialysis (PD) catheter insertion, so the preferred method usually depends on each centers experience. In our center we perform both percutaneous technique with fluoroscopic guidance (PTFG) and laparoscopic technique (LT). Objective: Our main goal is to present our experience with PTFG and our results. We also aim to compare PTFG with LT in terms of complications associated with catheter placement and 1-year catheter survival. Methods: We performed a retrospective study that included the 17 incident patients submitted to first PD catheter placement using PTFG from 28th October 2014 to 15th March 2018 and the last equivalent number of patients that were submitted to first PD catheter placement using LT, until 15th March 2018. Results: We observed no statistically significant differences between groups with respect to 1-year catheter survival and complications related to PD catheter insertion, apart from dialysate leakage, which was higher in the LT group. There were complications to take into account in the PTFG group. Conclusion: PTFG performed by nephrologists seems to be an effective technique for PD catheter placement, although no substitution for surgical techniques when clinically indicated, and results can be improved with increased experience with this technique.